Tantangan dan Adaptasi Orang Tua dalam Membesarkan Anak Berkebutuhan Khusus - Sany Salsabillah; Sri Nurhayati Selian (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This study aims to thoroughly analyze the various difficulties and coping strategies faced by parents when raising children with special needs (ABK). The primary rationale for this study is the increasing number of children with special needs in Indonesia and the complexity of parents' roles in supporting their development. This study employed a qualitative, descriptive phenomenological method involving three participants: parents of children with special needs in Banda Aceh City. Data were collected through interviews, direct observation, and document review, which were then processed using thematic analysis techniques. The results revealed that parents experience similar challenges, although their intensity varies depending on the age and severity of the child's condition. Furthermore, the parents' adaptations in this study were proactive and based on cultural values, enabling them to persevere despite significant challenges. These findings are expected to serve as a reference for the government, experts, and educational institutions in developing more effective support programs for families with children with special needs.